The dawn of X‐ray spectroscopy†. (12th April 2013) - Gerward, L.
Abstract : This paper describes a few episodes from the early days of X‐ray spectroscopy. It relies on contemporary publications, especially those by Barkla, Moseley, Siegbahn, and Compton. The paper addresses the subject from the vantage point of physics and should be of interest to the X‐ray spectroscopist, who wants to obtain a glimpse of the history of his chosen field. Copyright © 2013 John Wiley & Sons, Ltd.